A Narrative Inquiry into the Cultivation of a Classroom Knowledge Community in a Chinese Normal University - Libo Zhong; Cheryl J. Craig (Education Sciences)
This narrative inquiry explores a vibrant classroom knowledge community in a Chinese normal university. By examining the teacher’s interactions, we analyze the community’s development through three perspectives: (1) the author’s narrative of the course outline, (2) the teacher’s narrative of classroom culture, and (3) students’ narratives of their growth. The author presents a student-centered model and seven steps for enacting the course, outlining the environment for cultivating the knowledge community. The teacher’s narrative reveals clues to his success, emphasizing his use of storytelling to foster the community and share educational ideas. Students’ narratives reflect their growth, validating the classroom as a safe space for development and language learning. The significance of this research is that the classroom knowledge community consisted of the teacher, his undergraduate students, and his post-graduates. The three layers existed because of this unrestrained character, devoid of conflicts of interest, created a safe place for students’ development. This research study adds to the literature on how knowledge communities form in school contexts. It focuses on a particular space and time and involves multiple layers of participants, which is prerequisite to the conceptualization of classroom knowledge community. This research has important implications for college language education.